Effects of Omega-3 Polyunsaturated Fatty Acids on Platelet Function in Healthy Subjects and Subjects with Cardiovascular Disease - McEwen, Bradley J.; Morel-Kopp, Marie-Christine; Chen, Walter; Tofler, Geoffrey H.; Ward, Christopher M. (Seminars in Thrombosis and Hemostasis, 2013)
Hyperactivation and aggregation of platelets play a major role in thrombosis and hemostasis. The aims of this study were to investigate the effects of omega-3 polyunsaturated fatty acids (PUFAs) on platelet function. Light transmission aggregometry and flow cytometric analyses of platelet activation and platelet–leukocyte aggregates were determined at baseline and after 4 weeks of omega-3 (docosahexaenoic acid 520 mg and eicosapentaenoic acid 120 mg) supplementation. In total, 40 healthy subjects and 16 patients with a history of cardiovascular disease (CVD) completed the study. In healthy subjects, omega-3 PUFA significantly reduced adenosine diphosphate (ADP)–induced (maximum amplitude, 77.0% ± 3.2% vs. 71.6% ± 3.4%, p = 0.036; maximum slope, 86.3 ± 1.8 vs. 80.7 ± 2.1, p = 0.014) and adrenaline-induced platelet aggregation (maximum slope, 42.8 ± 2.7 vs. 37.4 ± 3.0, p = 0.013; lag time, 00:21 ± 00:02 vs. 00:31 ± 00:03 s, p = 0.002). Omega-3 PUFA also reduced P-selectin expression (40.5% ± 2.9% vs. 34.4% ± 2.4%, p = 0.049) on platelets and platelet–monocyte aggregates (38.5% ± 2.6% vs. 31.4% ± 2.5%, p = 0.022) after activation with ADP 0.5 µM. There were fewer changes in platelet aggregation and activation found in subjects with CVD. Nevertheless, there was a reduction in the slope of arachidonic acid–induced platelet aggregation (13.21 ± 6.41 vs. 4.88 ± 3.01, p = 0.009) and increased lag time for U46619 (00:16 ± 00:00 vs. 00:29 ± 00:07 s, p = 0.018) induced platelet aggregation. Thus, 4-week supplementation of 640 mg omega-3 PUFA reduced measures of platelet aggregation and activation in healthy subjects but effects were less evident in patients with existing CVD. Our findings support the recommendation that the omega-3 PUFA dose be higher in CVD than among healthy subjects.
Keywords: cardiovascular disease; omega-3 PUFA; platelet activation; platelet aggregation; thrombosis